Ancient Respected and Modern Absorbed, Chinese Essence and Western Utility—Thoughts of the Integrated Chinese Medicine and Western Medicine - Liu, Xiaofa; Li, Diangui; Lu, Shengda (Chinese medicine and natural products, 2022)
Traditional Chinese medicine (TCM) and Western medicine are two medical systems formed in different cultural backgrounds. The differences between them are that TCM focuses on the study of the invisible state while Western medicine focuses more on the study of the visible state of the human body; TCM pays attention to systematicity and integrity, while Western medicine pays attention to local evidence; TCM attaches importance to dialectical thinking, while Western medicine attaches importance to materialistic thinking. For the development of TCM, it is necessary to take the initiative to learn from and absorb all the advanced scientific and technological achievements in the world today. To innovate TCM, it is necessary to need to adhere to (1) the integration of “research on TCM with the thought of TCM ” and “research on TCM based on the thought of Western medicine”; (2) the integration of scientization of TCM and scientization for TCM; (3) the integration of mobilization therapy and allopathic therapy; (4) the integration of treating patients and treating diseases; (5) the integration of preventive treatment and existent disease treatment; (6) the integration of individuality and commonality; and (7) the integration of the macro and the micro.
Keywords: integrated Chinese medicine and Western medicine; TCM; Chinese essence and Western utility; theoretical innovation